2007
DOI: 10.1175/jcli4016.1
|View full text |Cite
|
Sign up to set email alerts
|

The Scripps Coupled Ocean–Atmosphere Regional (SCOAR) Model, with Applications in the Eastern Pacific Sector

Abstract: A regional coupled ocean–atmosphere model is introduced. It is designed to admit the air–sea feedbacks arising in the presence of an oceanic mesoscale eddy field. It consists of the Regional Ocean Modeling System (ROMS) and the Regional Spectral Model (RSM). Large-scale forcing is provided by NCEP/DOE reanalysis fields, which have physics consistent with the RSM. Coupling allows the sea surface temperature (SST) to influence the stability of the atmospheric boundary layer and, hence, the surface wind stress an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
89
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 110 publications
4
89
1
Order By: Relevance
“…Indeed some investigators (33)(34)(35)(36) emphasize the role of local air-sea feedbacks arising from ocean mesoscale features. For example, Chelton et al (36) showed that an oceanatmosphere coupling is observed in the California Current System during summer.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed some investigators (33)(34)(35)(36) emphasize the role of local air-sea feedbacks arising from ocean mesoscale features. For example, Chelton et al (36) showed that an oceanatmosphere coupling is observed in the California Current System during summer.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, fully coupled atmosphere-ocean RCMs have been used for dynamic downscaling studies (e.g., Aldrian et al, 2005;Ren and Qian, 2005;Seo et al, 2007;Artale, et al, 2010;Ratnam et al, 2013). In general, these studies reported an improvement in dynamic downscaling due to coupled models.…”
Section: Temporal Variability and Possible Impact Due To Coupled Oceamentioning
confidence: 99%
“…We also developed the Scripps Coupled Ocean-Atmosphere Regional (SCOAR) model (Seo, Miller and Roads, 2007a), which includes the Regional Spectral Model for the atmosphere (Juang and Kanamitsu, 1994) and the Regional Ocean Modeling System (ROMS) for the ocean (Haidvogel et al 2000;Shchepetkin and McWilliams 2005). SCOAR has been remarkably successful in simulating mesoscale ocean-atmosphere coupling for Pacific tropical instability waves (TIW's), mesoscale eddies in the California Current System (Figure 5), and gap winds along the Central American Coast (Seo et al, 2007a).…”
Section: Regional Impacts Of Climate Changes In the North Pacific Ocementioning
confidence: 99%
“…SCOAR has been remarkably successful in simulating mesoscale ocean-atmosphere coupling for Pacific tropical instability waves (TIW's), mesoscale eddies in the California Current System (Figure 5), and gap winds along the Central American Coast (Seo et al, 2007a). These phenomena were modeled for the first time using high resolution and full coupling, with key aspects of model variables compared favorably with observations.…”
Section: Regional Impacts Of Climate Changes In the North Pacific Ocementioning
confidence: 99%